2021
DOI: 10.1093/gbe/evab017
|View full text |Cite
|
Sign up to set email alerts
|

Not Frozen in the Ice: Large and Dynamic Rearrangements in the Mitochondrial Genomes of the Antarctic Fish

Abstract: The vertebrate mitochondrial genomes generally present a typical gene order. Exceptions are uncommon and important to study the genetic mechanisms of gene order rearrangements and their consequences on phylogenetic output and mitochondrial function. Antarctic notothenioid fish carry some peculiar rearrangements of the mitochondrial gene order. In this first systematic study of 28 species, we analysed known and undescribed mitochondrial genome rearrangements for a total of eight different gene orders within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(66 citation statements)
references
References 105 publications
(125 reference statements)
8
58
0
Order By: Relevance
“…This change in selective pressure was detected in several components of the electron transport chain itself (SDHA, QCR1, NDUA8, COX41), amid signatures of relaxed selective pressure on other genes related to mitochondrial function detected under other GO terms (COA7, NDUA8, PRLD1). Similar results were obtained in a previous study for mitochondrially-coded genes for which a prevalence of relaxation of the selective pressure in comparison with the non-Antarctic notothenioids was detected (in particular for COX3, COB, NAD2, NAD4, and NAD6; Papetti et al, 2021). While this may be a result of increased oxygen saturation in cold Antarctic waters, this trend towards relaxation of selective pressure may also be a result of the reduction in resilience to thermal variability in these systems as suggested in prior work (Mark et al, 2012) and may have persistently influenced the inception of the evolution of cryonotothenioids.…”
Section: Genes Under Relaxed Selective Pressure From Chronic Cold-wat...supporting
confidence: 90%
“…This change in selective pressure was detected in several components of the electron transport chain itself (SDHA, QCR1, NDUA8, COX41), amid signatures of relaxed selective pressure on other genes related to mitochondrial function detected under other GO terms (COA7, NDUA8, PRLD1). Similar results were obtained in a previous study for mitochondrially-coded genes for which a prevalence of relaxation of the selective pressure in comparison with the non-Antarctic notothenioids was detected (in particular for COX3, COB, NAD2, NAD4, and NAD6; Papetti et al, 2021). While this may be a result of increased oxygen saturation in cold Antarctic waters, this trend towards relaxation of selective pressure may also be a result of the reduction in resilience to thermal variability in these systems as suggested in prior work (Mark et al, 2012) and may have persistently influenced the inception of the evolution of cryonotothenioids.…”
Section: Genes Under Relaxed Selective Pressure From Chronic Cold-wat...supporting
confidence: 90%
“…The phylogenetic relationships of the notothenioids have been studied for more than 2 decades. Recently, the phylogeny of this group has been reanalyzed and updated using a combination of mitochondrial (mt) and nuclear DNA markers, including 15 new complete and 2 partial mt genomes ( Papetti et al 2021 ). The study identified a number of novel rearrangements in the mt genomes, including an extremely rare inversion event in the Trematominae.…”
mentioning
confidence: 99%
“…The study identified a number of novel rearrangements in the mt genomes, including an extremely rare inversion event in the Trematominae. Papetti et al (2021) generated a new phylogeny which showed that the mt evolution of the notothenioids has been characterized by multiple, relatively rapid changes in mt gene order.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The exception was N. rossii where an “in house” de novo multi-tissue transcriptome assembly was used. The figure was drawn considering the relative evolutionary relationship between the six Antarctic fish species and the sub-Antarctic fish ( 35 , 64 ). Gene/transcript accession numbers are available in Supplementary Table 1 .…”
Section: Resultsmentioning
confidence: 99%